2020
DOI: 10.1002/jtr.2381
|View full text |Cite
|
Sign up to set email alerts
|

Role of tourism IT adoption and risk management orientation on tourism agility and resilience: Impact on sustainable tourism supply chain performance

Abstract: The study explored the influence of tourism IT adoption and risk management orientation on tourism supply chain agility and resilience that may impact sustainable tourism supply chain performance using dynamic capability view. The study gathered 302 perceptual responses from hotels and tour companies and analyzed using structural equation modeling in AMOS. The study also evaluated for invariance of the proposed model across hotels and tour companies. Furthermore, it also explored if tourism IT adoption and ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 60 publications
0
33
0
Order By: Relevance
“…Liu et al (2018) found shared values and organizational learning as key enablers of competitive advantage, when deployed through dynamic capabilities. While Mandal et al (2016) and Roy et al (2016) were the foremost to conceptualize TAGL and TREL using DCV, Mandal and Dubey (2020) further found the significant role of tourism IT adoption and risk management orientation as prominent enablers for TAGL and TREL. Their study (Mandal and Dubey, 2020) further suggested that TAGL and TREL can result in sustainable performance, when deployed appropriately.…”
Section: Implications For Theorymentioning
confidence: 96%
See 3 more Smart Citations
“…Liu et al (2018) found shared values and organizational learning as key enablers of competitive advantage, when deployed through dynamic capabilities. While Mandal et al (2016) and Roy et al (2016) were the foremost to conceptualize TAGL and TREL using DCV, Mandal and Dubey (2020) further found the significant role of tourism IT adoption and risk management orientation as prominent enablers for TAGL and TREL. Their study (Mandal and Dubey, 2020) further suggested that TAGL and TREL can result in sustainable performance, when deployed appropriately.…”
Section: Implications For Theorymentioning
confidence: 96%
“…While Mandal et al (2016) and Roy et al (2016) were the foremost to conceptualize TAGL and TREL using DCV, Mandal and Dubey (2020) further found the significant role of tourism IT adoption and risk management orientation as prominent enablers for TAGL and TREL. Their study (Mandal and Dubey, 2020) further suggested that TAGL and TREL can result in sustainable performance, when deployed appropriately. Hence TAGL and TREL are useful dynamic capabilities in tourism supply chains.…”
Section: Implications For Theorymentioning
confidence: 96%
See 2 more Smart Citations
“…To ensure sustainability, supply chains need to be resilient [15][16][17]. Sustainability has become a primary focus of supply chains, and resilience is necessary to achieve sustainability targets [18].…”
Section: Introductionmentioning
confidence: 99%